Absence of the interstitial cells of Cajal in a neonate with segmental dilatation of ileum - Tatsuma Sakaguchi; Yoshinori Hamada; Yusuke Nakamura; Hiroshi Hamada; A-Hon Kwon (Elsevier, 2016)
Segmental dilatation of intestine (SD) is a congenital disease characterized by localized bowel dilation with normal ganglion cells. Clinically, small intestinal type of SD frequently occurs in the neonatal period with pseudo-obstruction. Though many theories have been proposed regarding the pathogenesis, the disease etiology is unclear. Interstitial cells of Cajal (ICCs) have been ascribed as the pacemaker cells that coordinate peristaltic behavior and its disorder is the possible cause of intestinal pseudo-obstruction. Here, we report a rare case of SD observed the absence of ICCs in the dilated segment. A male neonate suffered abdominal distention and vomiting underwent segmental resection of the dilated ileum on the third day after birth. He was diagnosed with SD and his clinical course after surgery was uneventful. Immunohistochemically, c-kit positive cell was not identified around the ganglion cells in the resected specimen.